1997
DOI: 10.1097/00006254-199707000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Pubic Symphysis Separation

Abstract: Peripartum pubic symphysis separation is a recognized complication of pregnancy with incidence estimates ranging from 1:300 to 1:30,000. Characteristic symptoms of symphyseal separation include suprapubic pain and tenderness with radiation to the back of legs, difficulty ambulating, and occasionally, bladder dysfunction. Clinical history, presenting symptoms, and response to therapy are sufficient to make the diagnosis, although radiographic documentation of symphyseal separation by x-ray or ultrasound are fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(44 citation statements)
references
References 10 publications
1
37
0
6
Order By: Relevance
“…The present systematic review found use of physiotherapy as the main component of conservative treatment for the majority of women with SPD [1,4,7,10,12,[18][19][20][21]24,[27][28]. Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present systematic review found use of physiotherapy as the main component of conservative treatment for the majority of women with SPD [1,4,7,10,12,[18][19][20][21]24,[27][28]. Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although she returned to her normal activities 1 yr later, she had a residual 1.3 cm interpubic gap after 2 yr [1]. Snow and Neubert performed a retrospective case series study of 9 women with SPD (route of delivery: vaginal, number of infants delivered not specified) who received physiotherapy and TENS, in addition to bed rest, pain control with nonsteroidal anti-inflammatory drugs, and a pelvic girdle, but the authors did not describe any specific results [7]. Scriven et al analyzed 9 women with SPD (route of delivery: vaginal, 6 single babies and 3 twins, mean weight of babies 3.4 ± 0.8 kg) who received physiotherapy and supervised mobilization and reported a decrease in the interpubic gap from 2 cm on average to normal measures, but 4 women continued to have pubic pain, 2 had lower back pain, and 2 were severely incapacitated at the last follow-up, which was 37 mo later on average [26].…”
Section: Physiotherapymentioning
confidence: 99%
See 3 more Smart Citations